Libraries in the Age of Information Explosion: A Brief Exploratory Study (Journal of Informatics Education and Research, 2023)
Librarians face several difficulties in providing information support to users in e-forms of multidisciplinary and interacting subject areas. Different tools and technologies can be used in libraries to support user demands. Academic librarians today are also facing numerous challenges due to the phenomenal changes brought in by the higher system, especially with online and distance learning courses, e-learning systems, increased use of ICT, new and better ICT tools for information acquiring, storing, and sharing, the availability of resources over the internet, etc.